Regional irreversibility of mean and extreme surface air temperature and precipitation in CMIP6 overshoot scenarios associated with interhemispheric temperature asymmetries - P. J. Roldán-Gómez; P. De Luca; R. Bernardello; M. G. Donat; M. G. Donat (Earth System Dynamics)
Overshoot scenarios, in which the forcing reaches a peak before starting to decline, show non-symmetric changes during CO2-increasing and CO2-decreasing phases, producing persistent changes in climate. Irreversibility mechanisms, associated with (among other factors) lagged responses of climate components, changes in ocean circulation and heat transport, and changes in the ice cover, bring hysteresis to the climate system. This work analyzes simulations from the Coupled Model Intercomparison Project Phase 6 (CMIP6) to explore the relevance of these mechanisms in overshoot scenarios with different forcing conditions (SSP5-3.4OS and SSP1-1.9) and their impact on regional climates, with a particular focus on the degree to which changes in regional extremes are reversible. These analyses show that in scenarios with strong forcing changes like SSP5-3.4OS, the post-overshoot state is characterized by a temperature asymmetry between the Northern Hemisphere and Southern Hemisphere associated with shifts in the Intertropical Convergence Zone (ITCZ). In scenarios with lower forcing changes like SSP1-1.9, this hemispheric asymmetry is more limited, while temperature changes in polar areas are more prominent. These large-scale changes have an impact on regional climates, e.g., temperature extremes in extratropical regions and precipitation extremes in tropical regions around the ITCZ. Differences between pre- and post-overshoot states may be associated with persistent changes in the heat transport and a different thermal inertia depending on the region, leading to a different timing of the temperature maximum in different regions. Other factors like changes in aerosol emissions and ice melting may be also important, particularly for polar areas. Results show that irreversibility of temperature and precipitation extremes is mainly caused by the transitions around the global temperature maximum, when a decoupling between regional extremes and global temperature generates persistent changes at regional level.